Primordial dusty rings and episodic outbursts in protoplanetary discs. Issue 3 (8th September 2022) - Kadam, Kundan; Vorobyov, Eduard; Basu, Shantanu
ABSTRACT: We investigate the formation and evolution of 'primordial' dusty rings occurring in the inner regions of protoplanetary discs, with the help of long-term, coupled dust-gas, magnetohydrodynamic simulations. The simulations are global and start from the collapse phase of the parent cloud core, while the dead zone is calculated via an adaptive α formulation by taking into account the local ionization balance. The evolution of the dusty component includes its growth and back reaction on to the gas. Previously, using simulations with only a gas component, we showed that dynamical rings form at the inner edge of the dead zone. We find that when dust evolution, as well as magnetic field evolution in the flux-freezing limit are included, the dusty rings formed are more numerous and span a larger radial extent in the inner disc, while the dead zone is more robust and persists for a much longer time. We show that these dynamical rings concentrate enough dust mass to become streaming unstable, which should result in a rapid planetesimal formation even in the embedded phases of the system. The episodic outbursts caused by the magnetorotational instability have a significant impact on the evolution of the rings. The outbursts drain the inner disc of grown dust, however, the period between bursts is sufficiently long for the planetesimal growth via streaming instability. The dust mass contained within the rings is large enough to ultimately produce planetary systems with the core accretion scenario. The low-mass systems rarely undergo outbursts, and, thus, the conditions around such stars can be especially conducive for planet formation.